Neoproterozoic mafic dyke swarms at the northern margin of the Tarim Block, NW China: Age, geochemistry, petrogenesis and tectonic implications - Zhang, C.; Li, Zheng-Xiang; Li, X.; Ye, H. (Pergamon-Elsevier Science Ltd, 2009)
Zircon and baddeleyite U-Pb ages and geochemistry of the Neoproterozoic mafic dyke swarms at the northern margin of the Tarim Block, NW China, are reported here to decipher the regional Neoproterozoic tectonic evolution. The mafic dyke swarm in Aksu and the mafic dyke swarm in Quruqtagh were emplaced at 759 7 and 773 3 Ma, respectively. The samples from Quruqtagh dykes are tholeiitic in major element compositions, enriched in LILE and LREE and depleted in HFSE and HREE. Isotopically, they are characterized by large ranges of ENd(t) values (from -7.1 to 1.8) and initial 87Sr/86Sr ratios (from 0.699 to 0.708). The Aksu mafic dykes share most geochemical characteristics of the Quruqtagh mafic dykes except that they are more highly evolved and with ENd(t) values ranging from -6.4 to -5.8. Geochemical features suggest that the Aksu mafic dykes and Quruqtagh mafic dykes were likely crystallized from a similar parental magma (possibly of high MgO contents) derived from a metasomatized SCLM (sub-continental lithosphere mantle) in a non-orogenic setting. In combination with other reported Neoproterozoic igneous rocks throughout the Tarim Block, there appear to be two major phases of Neoproterozoic igneous activities at ca. 820-800 and ca. 780-750 Ma, respectively. These two phases of igneous activities were concurrent with those in many other Rodinian continents and were most likely related to mantle plume activities during the break-up of the supercontinent Rodinia.